Characterisation of allelochemical compounds in Rhizophora apiculata and Acrostichum aureum of mangrove forest species - Othman, Rashidi; Ramya, Razanah; Mohd Hassan, Norazian (2018)
Rhizophora apiculata and Acrostichum aureum are a common mangrove species in Malaysia. Allelochemical interaction of the mangrove species was speculated to play an important role in the dominance in a harsh environment. This study assessed the quantitative and qualitative determination for total phenolic content and individual phenolic compounds as allelochemical content for R. apiculata and A. aureum leaves as potential allelopathic substance and evaluation of the ecological role of the substance. Two types of maceration extraction; water extraction and sequential alkaline extract were used for allelochemical screening analysis. Both extractions were separated by different solvents polarity; hexane, petroleum ether, ethyl acetate, butanol, and ethanol. A. aureum had the highest total phenolic contents (1129.52 GAE/g DW) as compared to R. apiculata. Meanwhile, the highest phenolic compound was detected in ethanol separation for A. aureum at 2176.83 ug/g DW as caffeic acid followed by vanillic acid, ferulic acid,4-hydroxybenzoic acid, trans-p coumaric acid, 2-coumaric acid and 3-coumaric acid respectively. Interestingly, only A. aureum was identified with seven phenolic compounds in sequential alkaline extraction. Therefore, A. aureum may work as an allelochemical producer and can contribute to the establishment of pure colonies of A. aureum in the mangrove ecosystem.